2019
DOI: 10.1038/s41598-019-38514-w
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative contexts predict duration of pig vocalisations

Abstract: Emotions are mental states occurring in response to external and internal stimuli and thus form an integral part of an animal’s behaviour. Emotions can be mapped in two dimensions based on their arousal and valence. Whilst good indicators of arousal exist, clear indicators of emotional valence, particularly positive valence, are still rare. However, positively valenced emotions may play a crucial role in social interactions in many species and thus, an understanding of how emotional valence is expressed is nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
8
33
0
Order By: Relevance
“…The piglets expressed a similar frustration state during the anticipation phase as when the entrance of any (pseudo)social partner was delayed. We found an average duration for the phase of (0.31 < 0.35 < 0.39, table S4 ), value that are similar to what Briefer et al 19 found for negative contexts. This result is surprising because our behavioural data show that additional contact has a positive effect on the human-piglet relationship (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The piglets expressed a similar frustration state during the anticipation phase as when the entrance of any (pseudo)social partner was delayed. We found an average duration for the phase of (0.31 < 0.35 < 0.39, table S4 ), value that are similar to what Briefer et al 19 found for negative contexts. This result is surprising because our behavioural data show that additional contact has a positive effect on the human-piglet relationship (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…When the arrival of the partner was delayed, the duration of the piglets’ grunts increased for both partner types. Longer grunts had already been associated with a negative emotional valence 19 , 20 , 35 , which confirms that delaying the arrival of the partner led to a negative emotional state in comparison to the initial phase: a discrepancy from expectation that produced something like frustration. These results allow us to conclude that we did succeed in generating a specific anticipatory state during the tests which was expressed both behaviourally and vocally.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…When the arrival of the partner was delayed, the duration of grunts increased for both partner. Longer grunts had already been associated to negative emotional valence 18,19,28 , which confirms that the delay lead in piglets to a negative emotional state, a situation of non-correspondence with expectation, whatever the partner. These results allow us to conclude that we did succeed in generating a specific anticipatory state during the tests.…”
Section: Discussionsupporting
confidence: 56%
“…This latter phase is certainly a context with a negative valence (social isolation) and piglets may express the negative valence of this context in the duration of their grunt. In fact, several examples of the literature show that grunt duration is higher in negative contexts 18,28 . The duration of piglets’ grunt was not changed during anticipation.…”
Section: Discussionmentioning
confidence: 99%